الإعراب التقديري في اللغة العربية ونماذجه في القرآن الكريم - Hasnah, Nur (Al-Uslub: Journal of Arabic Linguistic and Literature, 2019)
Arabic is a language that has many features compared to other languages ​​in this world. Among the privileges is I’rab. I'rab is a condition of the change in the last line of a word in a sentence due to the variety of amyl or its amendment Without Arabic I’rab, it would be difficult to sort out the meaning of words arranged in a discourse. With I'rab known easily words that are located as mubtada’ (subject in the number of ismiyyah), Khabar (predicate) etc. and will not cause misunderstanding of meaning. I’rab consists of three types namely Lafzhi, Taqdiri and Mahalli. I’rab Taqdiri is the final change of words in an invisible sentence caused by the letter ‘Illat. This research was conducted by the method of library research or the study of literature sourced from the books of syntax (nahwu) and al-Qur’an al-Karim. The author looks at the theoretical places I'rab taqdiri in Nahwu's book and sees an example in the Qur'an.